PEMBATALAN SERTIPIKAT HAK MILIK OLEH KANTOR PERTANAHAN BERDASARKAN PUTUSAN PENGADILAN YANG TELAH BERKEKUATAN HUKUM TETAP DALAM PERKARA NOMOR:17/PDT.G/2009.PN.LB.BS - Roni, Roni; Daulay, Zainul; Benni, Beatrix (Universitas Ekasakti, 2020)
One of the objectives of land registration is to provide legal certainty for land rights holders. Therefore, in order to make this happen, regulations regarding land registration are made, one of which is Article 32 paragraph (2) PP Number 24 of 1997. However, in reality there are still problems in terms of ownership of a parcel of land associated with this article, namely against a plot of land which has been controlled by a legal subject for years and has been equipped with a certificate. There are still outsiders demanding rights to the land with respect to the land. Until now, Article 32 paragraph (2) Government Regulation Number 24 Year 1997, which should have been a solution to the above problems, still creates differences. Given the existence of this article is not in accordance with the negative publication system adopted by land registration in Indonesia, where a certificate is not an absolute evidence, but a certificate is strong evidence.